PENGEMBANGAN BAHAN AJAR BERDASARKAN PENDEKATAN SAINTFIK UNTUK SISWA SMP NEGERI 2 SUNGAI LIMAU - Cici Ramayani; Delfianto Delfianto (STKIP Pesisir Selatan, 2019)
AbstractProblems found in Sungai Limau 2 Public Elementary School toward teacher books and student books that researchers did still find material substance that is not in accordance with the 2013 curriculum. This research is research & development (R & D). This study aims to describe the feasibility of teaching materials in validity, effectiveness and practicality. Research and development is a research method used to develop or validate products used in education and learning. The development of teaching materials is based on the development of the ADDIE model (analysis, design, develop, implement and evaluation). First, the analysis phase is the first stage carried out by someone developing a learning module. Secondly, the design is based on what has been formulated in the analysis phase. Third, the development stage, namely the production stage, everything that has been made in the design stage is then realized. Fourth, the implementation phase is the implementation of the learning module that is ready for student use. Fifth, evaluation phase, which can be done in formative and summative forms.The results of the study show that short story text teaching materials based on the developed scientific approach are valid, practical, and effective.